Impact of clinical factors on the diagnostic performance of diffuse optical spectroscopic imaging for breast cancer - Yeji Kwon; Jiyoung Yoon; Chanhui Lim; Heesun Hong; Sung-Ho Han; Min Jung Kim (Scientific Reports)
Abstract Due to insufficient sensitivity of mammography in dense breasts, ultrasonography and MRI have been incorporated into breast screening, despite increasing false positive risks. While optical imaging has been suggested to improve specificity, its effectiveness in diagnosing breast lesions remains unclear. This study investigates the impact of clinical factors on the diagnostic performance of diffuse optical spectroscopic imaging (DOSI) for detecting breast malignancies. Between March and May 2022, 62 women with 62 breast lesions (37 malignant, 25 benign) were analyzed using DOSI to quantify the concentrations of tissue chromophores (HbO2, HHb, water, lipid), total hemoglobin concentration (THC), oxygen saturation (StO2) and tissue optical index (TOI). The ratio of each parameter was compared to those of contralateral normal breasts, and diagnostic performance was assessed using area under the curve (AUC) values. The TOI ratio demonstrated the highest AUC (0.904, 95% CI 0.831–0.977), followed by water (0.836, 95% CI 0.736–0.936) and THC (0.738, 95% CI 0.613–0.864). The TOI ratio showed no significant differences in diagnostic performance based on clinical factors, whereas the water and THC ratios varied according to breast thickness, nipple distance, and BMI. Overall, the TOI ratio demonstrated strong diagnostic performance, suggesting its potential for universal application in breast cancer diagnosis.